2004
DOI: 10.1002/cjg2.506
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Magnetic Index Abnormal Change in Solar Magnetic Field on Climate at Middle Latitude of North Hemisphere

Abstract: In this paper, based on the characteristics of the sunspot number, the time sequence of the magnetic index of the sunspot magnetic field is established. The analysis of temperature field spectrum shows that in the air temperature field of the troposphere and stratosphere at the middle latitude of Northern and Southern hemispheres there generally exist cycles with a 22‐year period. The analysis also shows that the cycle of the air temperature field with a 22‐year period is generated by the solar activity with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…Two important conditions for excitating geophysical events are high speed solar wind carrying enough energy and planetary magnetic field. The above analysis shows the important influence of the solar magnetic direction variation on the tropospheric air temperature anomaly sign, suggesting that the significant 22-year periodic variability of the air temperature in the northern hemisphere is excitated by the solar activity [29] , and is response to the intensity and direction variations of the solar magnetic field. The temperature curve in Fig.1 is not so regular like the MI curve, because except for solar activity, the air temperature is also impacted by other factors, whose influence is far less than that of solar activity.…”
Section: Solar Magnetic Variation and Climate Effect Induced By MImentioning
confidence: 84%
See 1 more Smart Citation
“…Two important conditions for excitating geophysical events are high speed solar wind carrying enough energy and planetary magnetic field. The above analysis shows the important influence of the solar magnetic direction variation on the tropospheric air temperature anomaly sign, suggesting that the significant 22-year periodic variability of the air temperature in the northern hemisphere is excitated by the solar activity [29] , and is response to the intensity and direction variations of the solar magnetic field. The temperature curve in Fig.1 is not so regular like the MI curve, because except for solar activity, the air temperature is also impacted by other factors, whose influence is far less than that of solar activity.…”
Section: Solar Magnetic Variation and Climate Effect Induced By MImentioning
confidence: 84%
“…According to the relation between the maximum magnetic field intensity B m and relative number R of the sunspots [29] :…”
Section: Establishment Of the Sunspot Magnetic Index (Mi)mentioning
confidence: 99%
“…Solar variation plays an important role in affecting changes in weather, space weather and climate on Earth (Camp and Tung 2007). Some researches (Qu et al 2004;Cong et al 1995) indicated that the sun activities influence the condition of climate and atmosphere by way of radiation changes and inspiring the magnetic field change in the earth, thus affecting the climate in the earth. The two ways are closely related to the magnetic field changes in the sunspot activities.…”
Section: The Period Of Dry and Wet Condition In The Wei River Basinmentioning
confidence: 99%
“…Friis-Christensen and Lassen (1991), Haigh (1996), Sharp (2013), Mörner (2010), Zhao and Feng (2014), Liu et al (2011), and Zhao et al (2011) successfully investigated the changes in surface environment and global climate on the basis of solar activity. Qu et al (2004) put forth a similar theory of the changes in surface environment and global climate with solar activity. Several theories have Note: These are basic data from NASA.…”
Section: Introductionmentioning
confidence: 99%